Anaplastic lymphoma kinase-positive diffuse large B-cell lymphoma presenting in nasal cavity: a case report and review of literature - Chen, Ji (Int J Clin Exp Pathol, 2015)
Anaplastic lymphoma kinase (ALK)-positive diffuse large B-cell lymphoma (DLBCL) is a rare subtype of non-Hodgkin’s lymphoma (NHL) with distinct morphologic and immunohistochemical features. We reported a 57-year-old female with ALK-positive DLBCL in her left nasal cavity. Histologically, the tumor cells were characterized by plasmablastic morphology and tested positive for ALK in a cytoplasmic granular staining pattern. The neoplastic cells were positive for CD38, CD4, MUM1, CD138 and Vimentin. However, they failed to express CD56, CD30, as well as mature B cells markers, such as CD79a, CD20 and T cells markers such as CD2, CD3, CD5, CD7 and CD8. The patient achieved complete response after four cycles of CHOEP (cyclophosphamide, doxorubicin, vincristine, prednisone, and etoposide) treatment. Then she received radiotherapy of the originally involved area. This case represented a rare ALK-positive DLBCL in the nasal region.